PENGARUH KEPRIBADIAN DAN PEMBERDAYAAN TERHADAP KINERJA MELALUI ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN MODAL SOSIAL SEBAGAI VARIABEL MODERATING - Rahayu, Sri; Abdul Rozak, Hasan (Proceeding SENDI_U, 2015)
This study aims to analyze the influence of Personality and Performance through Empowerment againstOrganiztional Citizenship Behavior moderated by social capital Population Council Representative Officer atthe National Family Planning Central Java Province. This research is expected to produce a useful analysis toprovide empirical information about the influence of personality, empowerment, organizational citizenshipbehavior on employee performance with moderated social capital can be considered toimprovehumanresources.To examine the relationship between variables, the researchers used a techniqueCensus, Data analysis using SPSS 20.00. Data were collected by using a questionnaire given to respondentsstudy population 149 employees and entirely used as samples, while the samples were processed 118respondents. Tests on research conducted by the test instrument validity (factor analysis) and coefficient alphareliability test while statistical testing tool used is multiple regression analysis, t test, test and test R2moderation. The results showed that personality positive and significant effect on OCB, Empowerment positiveand significant effect on OCB, Personality positive and significant impact on employee performance,Empowerment positive and significant impact on performance, OCB positive and significant impact onemployee performance, Personality no positive effect and significant impact on performance, Empowermentpositive and significant impact on performance, OCB is not positive and significant impact on performance, testresults showed that the OCB mediation mediate the effect of empowerment on employee performance, but OCBdoes not mediate the effect of personality on employee performance. The test results show that social capitalmoderation appropriately used as a moderating variable, which acts to moderate the relationship betweenempowerment employee performance.Keywords: Personality, Empowerment, OCB, performance and social capital